WHITE TAILED JUNGLE RAT MORPHOLOGICAL DIVERSITY STUDY (Maxomys sp.) OF NORTH SULAWESI ACCORDING FROM THE TAIL MORPHOLOGICAL CHARACTERISTICS - frisky fransiskus patuwo; Decky D. W. Kamagi; Mariana Rengkuan (Universitas Negeri Manado, 2022)
Tail characteristics of the White-Tailed Jungle Rat (Maxomys sp.) of North Sulawesi have been examined by us to reveal the population diversity. Usually, examining population diversity or species uses numerous morphological features as markers for variation. However, in this study, we are only using one morphological feature, which is the characteristic of the tail from the samples. Several experts have used tail characteristics as the sole identifier for species identifications. On another account, diversity studies using various white-tailed jungle rats are also being performed, and the result of the said study can be compared with the result of the study in which only a single feature is the tail characteristics of the white-tailed jungle rat. The characteristics of white-tailed jungle rats that were examined include total length, the total length of the white section and the present/lack of fine hairs on the tip. The number of samples is 35. The samples are obtained from the jungles of North Sulawesi, which are The District of Minahasa, North Minahasa, South Minahasa, and Southeast Minahasa. The results of morphological observation of the white-tailed jungle rat were analyzed using mutual cluster analysis, statistics program, SPSS IBM, 26. The analysis results from a dendrogram showed two main clusters: the first with the numbers 9, 19 and 12 and the second with the remaining sample numbers. On the second cluster, there are two more formed sub-cluster. The results of this study are nearly identical to the study results that use various morphological diversities. This study recommends that the tail characteristics of a white-tailed rat can represent the diversity of white-tailed rats.